Communication and raising public awareness in promoting drinking water safety, hygiene and health - SILITRARI, Natalia; SALARU, Ion (One Health & Risk Management, 2022)
Introduction. Access to safe water and hygiene is a precondition for a healthy life. In the Republic of Moldova, it has been estimated that the incidence of acute diarrhea and hepatitis A is about 15-20%, gastrointestinal diseases account for 22-25% and 100% of dental fluorosis are caused by the drinking water quality.Effective communication with the population in order to prevent diseases related to water quality and poor hygiene, protection and management of water resources, and rational use of water are essential elements in the development and implementation of national environmental and health policies. One of the objectives of the National Program for the Implementation of the Protocol on Water and Health is to increase the level of relevant knowledge on drinking water safety, hygiene and health among population up to 80% by 2025 and up to 85% by 2030.Material and methods. The purpose of this research was to evaluate the effectiveness of communication and awareness-raising activities on drinking water, hygiene and health. The communication and information interventions carried out in the Republic of Moldova over the last 10 years were evaluated, as well as the review of the specialized literature in the field of health communication in relation to the environment.Results. Communication and information dissemination to the public on water and health issues is carried out in the following ways, including: (i) Publication of regular official reports. These reports are prepared and published annually on the official websites of the authorities (National Agency for Public Health, Ministry of Environment, State Ecological Inspectorate, etc.) and contain data on water quality from various sources, access to improved water systems and disease incidence, water protection measures, pollution prevention and impact prevention. It should be noted that these reports are written in an academic, technical style that is often difficult to understand for most of population. (II) World Days Awareness Campaigns. World Water Day (March 22) and International Handwashing Day (October 15) are marked annually. The actions carried out during these events usually focus on information through the media, training of specialists, policy dialogues at different levels, media coverage through social networks, distribution of information materials, interpersonal communication, etc. Such actions are usually not financially supported and with a less impact on the authorities and the population. (iii) Communication and awareness campaigns on raising the level of knowledge, attitudes and practices. These actions aim to change knowledge, attitudes and/or behaviors regarding a certain issue related to water quality, sanitation or hygiene, and are carried out in a certain period of time, with planned objectives and achievable results.Conclusions. Effective communication with the public and active dissemination of information are the key elements in the development and implementation of environmental and health policies. Communication mechanisms, in terms of educational activities and public awareness and information campaigns, are regularly used tools to increase understanding the relationship between water and health at the Community level.